Bunker risk management strategies in liner shipping companies part III : financial instruments to reduce bunker price risk - Yeo, Edmund Wen Jie. (2012)
The increasing bunker price pressure resulted in the liner shipping industry seeking alternatives to mitigate bunker price risk by looking into non-core competencies such as financial hedging. However, there is generally a lack of research into how liner shipping companies can make use of hedging instruments effectively. This report compared bunker futures and forwards; reviewed the current bunker futures market; and studied the effectiveness of bunker futures and crude oil futures in intercontinental liner trade. The results showed that bunker futures hold certain advantages that forwards cannot provide but suffer from weaknesses due to the lack of market interest.